Os efeitos do contaminante emergente lítio e da suplementação com selênio sobre a metamorfose de girinos de rãs-touro, Lithobates catesbeianus - Vidal, Felipe Augusto Pinto (2019)
Most of the pollutants discarded into the environment, such as lithium and selenium, are still lacking in studies of the effects that they cause in nature and are therefore called emerging pollutants. The objective of this study was to evaluate the effects of concentrations considered safe by the Brazilian Environmental Council (CONAMA) (2.5 mg.L-1 for lithium and 0.01 mg.L-1 for selenium) over morphometric, behavioral, biochemical and histological parameters of bullfrog tadpoles (Lithobates catesbeianus) during the metamorphic process. For that, we used isolated exposures of each of these elements, as well as a group exposed to the two elements combined. Our work showed that when animals were exposed to lithium and selenium plus lithium, there was a significant decrease in activity level both after 7 days of exposure and after 21 days of exposure. The analysis of the activity of the lactate dehydrogenase (LDH) enzyme of the tail muscle showed a reduction only in the groups exposed to selenium plus lithium, both after 7 and after 21 days. Hepatic glucose mobilization was higher in the lithium and selenium plus lithium groups on day 7. In the 21st day, what we saw was a reduction of hepatic glucose mobilization in the group exposed to selenium. The mobilization of glucose in the tail muscle tissue did not change in any of the scenarios. We observed an increase in the mobilization of triglycerides in all groups exposed, both on the 7th and 21st days. In turn, the mobilization of triglycerides in tail muscle tissue showed no changes. Liver and caudal muscle protein levels showed no difference for any group in any of the periods tested. The histological analyzes of the thyroid tissue and skin were performed only on the 21st day, so we observed a decrease in the total area of the gland, a decrease in the area of the follicles, as well as a decrease in the total number of follicles for all exposed groups. When analyzed longitudinal sections of the animals' skin, we observed that for all groups there were thickening of the epidermis. Thus, we can say that exposure to these elements, even in concentrations allowed by the Brazilian environmental agency, showed that there may be damage to the normal development of L. catesbeianus tadpoles. Thus, it is hoped that with the results obtained, issues of ecological and preservationist importance will be discussed not only in the scientific area, but also in the regulatory agencies.